Orthodontic extrusion as treatment option for crown-root fracture: literature review with systematic criteria - Faria, Lorraine Perciliano de [UNESP]; Almeida, Melyna Marques de [UNESP]; Amaral, Marina Fuzette [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Okamoto, Roberta [UNESP]; Mendonça, Marcos Rogério de [UNESP] (Jaypee Brothers Medical Publishing, 2015)
To review the literature searching for a consensus for the choice of orthodontic extrusion as treatment for crown-root fracture. An electronic search was performed in the databases PubMed, Cochrane Central Register of Controlled Trials and Scopus and a manual search of the Journal Dental Traumatology. Forty articles were found in PubMed and 38 in Scopus and after removal of duplicate sample 51 contained articles. Of these, 48 were excluded for not having orthodontic treatment, no follow-up or follow-up less than 6 months, or not report the presence of crown-root fracture. In manual search in Dental Traumatology 20 articles were found, but none of them met the prerequisites established. So, three articles formed the basis of the study. The choice of how to treat orthodontic extrusion of crown-root fracture was effective and stable, without root and periodontal changes. Factors, such as root formation and presence of pulp vitality were decisive for determining the stages of treatment, however, there is no consensus based on scientific evidence about these protocols.
Keywords: Orthodontic extrusion; Orthodontics; Tooth injuries